P117 Neutrophil chemotaxis in the sz form of alpha-1 antitrypsin deficiency. (15th November 2017) - Vayalapra, S; McGuinness, AJA; Stockley, RA; Turner, AM
Abstract : Introduction: Alpha-1 antitrypsin deficiency (AATD) is a genetic disorder which predisposes to the development of lung disease. The PiSZ phenotype is associated with a lower risk of disease and a pattern of emphysema more characteristic of patients with chronic obstructive pulmonary disease (COPD) than the PiZZ phenotype. Aberrant migration of neutrophils has been observed in stable COPD, possibly contributing to the pathogenesis. Neutrophils from PiZZ patients show a migratory phenotype similar to that of healthy controls and the migratory characteristics of PiSZ neutrophils have not been investigated. Methods: The chemotaxis of peripheral blood neutrophils in PiSZ patients was characterised using an Insall chamber and time-lapse video microscopy. Migratory characteristics of the neutrophils were compared with existing data from PiZZ and usual COPD patients. A marker of neutrophil elastase activity known as Aα-Val 360 was compared between patient groups and the relationship between patient characteristics and neutrophil migration was examined. Results: PiSZ neutrophils moved with a reduced velocity compared to cells from PiZZ patients in the presence of IL-8 (Mean (SEM): 0.156 (0.036) vs 0.308 (0.045); p=0.016). No difference was apparent in migrating velocity between PiSZ and PiMM neutrophils (Mean (SEM): 0.692 (0.150) vs 0.868 (0.344); p=0.6480). The PiMM COPD patients had higher levels of Aα-Val 360 when compared to PiSZ (Median (IQR): 25.3 (22.6) vs 14.2 (7.75); p=0.015) and PiMM (Control) patients (Median IQR: 25.3 (22.6) vs 15.9 (12.1); p=0.018). A correlation between alpha-1 antitrypsin level and migrating velocity was observed (r 2 =0.410, p=0.003). Conclusion: Neutrophils from PiSZ patients exhibited a migratory phenotype intermediate between PiZZ and usual COPD patients. Higher levels of Aα-Val 360 in COPD patients suggest that they have elevated levels of neutrophil elastase activity.